A review of non-precious metal single atom confined nanomaterials in different structural dimensions (1D–3D) as highly active oxygen redox reaction electrocatalysts. Issue 5 (15th January 2020) - Liu, Jin; Zhang, Hao; Qiu, Ming; Peng, Zehua; Leung, Michael K. H.; Lin, Wen-Feng; Xuan, Jin
Abstract : Different dimensional supports for non-precious-metal single-atom catalysts play significant roles in their fabrication and electrocatalytic activities for oxygen redox reactions. Abstract : Non-precious-metal single atom (NPM-SA) confined nanomaterials with maximum metal atom utilization have recently attracted particular interest, providing opportunities for exploiting novel heterogeneous electrocatalysts with low cost and high efficiency. The applications of non-precious-metal single-atom catalysts (NPM-SACs) have been extensively developed in electrochemical energy technologies such as fuel cells, metal–air batteries, and hydrogen production via water splitting. NPM-SACs can be confined on substrates with various structures and dimensions from 1D to 3D. However, the role of the structural dimensions of substrates has not been critically summarized. In this review, recent advances in NPM-SACs such as facile synthesis, characterization, performance in catalyzing oxygen redox reactions, and related applications are highlighted through a focus on different dimensional substrates (1D, 2D, and 3D). The general fabrication strategies and the catalytic mechanism of NPM-SACs in the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are extensively discussed. Moreover, the opportunities and challenges in this emerging field are presented on the basis of its current development.